NiTi Alloy Quasi-Zero Stiffness Vibration Isolation Structure with Adjustable Mechanical Properties - Qian Wu; Jianxiang Qiao; Xinping Li; Shengsheng Wang; Bingqian Li; Siyang Wu; Zhenguo Wang; Jiangtao Ji (Machines)
Despite the significant engineering applications of vibration isolation structures, there remain challenges in adjusting low-frequency isolation performance. To tackle this issue, this study proposes a temperature-controlled quasi-zero stiffness vibration isolation structure utilizing NiTi shape memory alloys. The stiffness and vibration isolation performance of the structure can be adjusted by modifying the heat treatment process and temperature variations of the alloy. The vibration isolation system is composed of vertical and horizontal alloy beams, with structural mechanics analysis performed to develop both static and dynamic theoretical models. The study investigates the effects of the heat treatment process on the phase transition characteristics and mechanical properties of nickel-titanium alloys, and analyzes the correlation between the heat treatment parameters of alloy beams and the stiffness performance of vibration isolation structures. By applying temperature variations to the alloy beams, the stiffness and vibration isolation performance of the entire structure can be dynamically adjusted. This research provides theoretical guidance for achieving adjustable vibration isolation performance across low-frequency and wide ranges, offering promising prospects for the application of vibration isolation structures in dynamic environments.